OPTIMIZING COLLABORATION: USING GOOGLE DRIVE EFFECTIVELY IN TEAMS - CARPIO MENDOZA, JANET (2024)
INTRODUCTION: THE GOOGLE DRIVE APPLICATION HAS SEVERAL RESOURCES THAT OPTIMIZE THE ORGANIZATION AND PLANNING OF ACADEMIC ACTIVITIES, SO IT IS APPLIED TO BENEFIT THE TEAMWORK DEVELOPED BY STUDENTS. METHODOLOGY: THE RESEARCH WAS OF A BASIC TYPE, WITH A QUANTITATIVE APPROACH AND A CAUSAL CORRELATIONAL LEVEL. THE SAMPLE CONSISTED OF 75 STUDENTS FROM A TECHNICAL-PRODUCTIVE EDUCATIONAL CENTER (CETPRO). THE APPLICATION COLLECTION TECHNIQUE WAS THROUGH OBSERVATION AND THE INSTRUMENT USED WAS THE CHECKLIST FOR BOTH VARIABLES. THE INSTRUMENTS WERE VALIDATED BY EXPERTS WHO DETERMINED THE EFFECTIVENESS, CLARITY AND COHERENCE OF THE CONTENT. RESULTS: ACCORDING TO NAGELKERKE, GOOGLE DRIVE PROVIDES BETTER LEARNING RESULTS, WITH A 50.2% INCIDENCE RATE, CONSIDERING THAT IT MAINTAINS A CONSTANT MOTIVATION OF THE STUDENTS, ALLOWING THEM TO PARTICIPATE ACTIVELY, PROMPTLY AND EFFICIENTLY SO THAT EVERYONE IS INVOLVED IN THE DEVELOPMENT OF THE ACTIVITY. CONCLUSIONS: IT WAS EVIDENCED THAT THE USE OF GOOGLE DRIVE OPTIMIZES THE DEVELOPMENT OF COLLABORATIVE WORK IN STUDENTS IN THE DIMENSIONS OF POSITIVE INTERDEPENDENCE, INDIVIDUAL AND GROUP RESPONSIBILITY, STIMULATING INTERACTION, INTERPERSONAL AND TEAM TECHNIQUES, AND GROUP EVALUATION. © 2024, HISIN (HISTORY OF INFORMATION SYSTEMS). ALL RIGHTS RESERVED.